Apoyo en la elaboración y control del presupuesto del proyecto multifamiliar Torres del Norte en la ciudad de Sogamoso (2022)
The following work is carried out during the development of the internship in the company GM Construcciones Asociados S.A.S located in the city of Sogamoso Boyacá, which designs, builds and sells real estate projects. Where it is currently in the construction of the Torres del Norte multifamily project, which consists of 3 apartment towers. Tower 3 of 8 levels, tower 2 of 10 levels and in tower 1 where the internship is developed, which consists of 12 levels where budget controls of the work will be carried out from the sixth plate to the tenth plate, which are construction phases in which that the student will be present. This document presents the report to the support in the project budgets where the necessary information is collected such as the project plans, material costs through billing and quotes and with this the calculations of the respective quantities of the project in the current phase are made. and the APU's necessary to calculate the direct costs of the project, this putting into practice the knowledge obtained by the intern.